Design and Development of An Employee Attendance Application Using Android-Based Location Based Service at Human Resources Service Company - Usmia, Sitti; Syahribulan; Syamsinar; Nur Mahmudah, Fitri; Munizu, Musran (Jurnal Informasi dan Teknologi, 2023)
The purpose of this study is to learn how to create an Android-based location-based service (LBS) application for employee attendance. The author employed four different approaches for gathering data for this study: literature studies, interviews, observation, and similar literature studies. Rapid Application Development (RAD), a system development approach that describes use case diagrams using Microsoft Visio software and UML tools, was employed in the preparation of this study. Requirement planning, RAD design workshop, and implementation are the three stages of the Rapid Application Development (RAD) system development approach. Using Microsoft Visio software to help with diagramming, researchers used UML (Unified Modeling Language) tools to begin creating an Android-based attendance application. It can be inferred from the description and discussion's outcomes that: With this research, employees who work in client offices will find it easier to take attendance because they do not need to go to the head office first but can take attendance directly at the client's office. With this research, the process of absenteeism, absence from work due to leave, permission, sickness, and calculation of overtime at the company becomes faster and easier because employees can do attendance, apply for leave, permission, overtime, and sickness directly via the Android application without having to open a browser first. formerly. With this Android application, it can add to the company's brand as a provider of HR management services.